RAGE-induced ILC2 expansion in acute lung injury due to haemorrhagic shock. Issue 3 (14th January 2020) - Zhang, Kai; Jin, Yue; Lai, Dengming; Wang, Jieyan; Wang, Yang; Wu, Xiaoliang; Scott, Melanie; Li, Yuehua; Hou, Jinchao; Billiar, Timothy; Wilson, Mark; Shu, Qiang; et al.
Abstract : Background: Type 2 immune dysfunction contributes to acute lung injury and lethality following haemorrhagic shock (HS) and trauma. Group 2 innate lymphoid cells (ILC2s) play a significant role in the regulation of type 2 immune responses. However, the role of ILC2 in post-HS acute lung injury and the underlying mechanism has not yet been elucidated. Objective: To investigate the regulatory role of ILC2s in HS-induced acute lung injury and the underlying mechanism in patients and animal model. Methods: Circulating markers of type 2 immune responses in patients with HS and healthy controls were characterised. Using a murine model of HS, the role of high-mobility group box 1 (HMGB1)-receptor for advanced glycation end products (RAGE) signalling in regulation of ILC2 proliferation, survival and function was determined. And the role of ILC2 in inducing type 2 immune dysfunction was assessed as well. Results: The number of ILC2s was significantly increased in the circulation of patients with HS that was correlated with the increase in the markers of type 2 immune responses in the patients. Animal studies showed that HMGB1 acted via RAGE to induce ILC2 accumulation in the lungs by promoting ILC2 proliferation and decreasing ILC2 death. The expansion of ILC2s resulted in type 2 cytokines secretion and eosinophil infiltration in the lungs, both of which contributed to lung injury after HS. Conclusions: These results indicate that HMGB1-RAGE signalling plays a critical role in regulating ILC2 biological function that aggravates type 2 lung inflammation following HS.